Kinetic investigations of phaseformation processes in the BaO-Al2O3-Fe2O3 system - Iloukha, Nikolay; Barsova, Zoya; Cwhanovskaya, Irina; Timofeeva, Valentina (Publishing House of Lviv Polytechnic National University, 2010)
The kinetic investigations of phase formation processes in the mixture which contains BaO, Al2O3, Fe2O3 were carried out. The degree of conversion and the activation energy were calculated, the dependence of the reaction rate and the rate constant on reaction temperature was determined. Проведено кінетичні дослідження процесів фазоутворення у суміші, що містить BaO, Al2O3, Fe2O3. Розраховані значення ступеня перетворення, енергії активації, записані рівняння для константи швидкості реакції, отримані залежності швидкості реакції від температури.
Кінетичне дослідження процесів фазоутворення в системі BaO-Al2O3-Fe2O3
Keywords: activation energy; reaction rate; rate constant; енергія активації; швидкість реакції; константа швидкості реакції